ELECTRONIC WORTH OF MOUTH AND DESTINATION IMAGE AND IT’S AFFECTS ON VISITING TOURISTS DECISION IN THE TIKUS ISLAND - Eska Prima Monique Damarsiwi; Wagini Wagini (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2018)
Tourism is one of the mainstays to obtain the country's foreign exchange and its development is expected to spur Indonesia's economic growth. Every area in Indonesia has the potential to be used as a tourist attraction, as well as the area of Bengkulu City which has exotic marine tourism, namely in Tikus Island. The purpose of this study was to analyze the effect of Electronic Word of Mouth (eWOM) on tourist visiting decisions to Tikus Island and to analyze the influence of Destination Image on tourist visiting decisions to Tikus Island and to analyze which variables had the most dominant influences of visiting tourists to Tikus Island. This research also has an output target that is expected to be achieved, including this research can provide input for the government and employers to find out Electronic Word Of Mouth (eWOM) and Destination Image so that it can ultimately increase tourist interest.. This research was conducted in the area of tourist objects that are often visited by local and outside tourists in the city of Bengkulu. The sampling method in this study is a survey using a cross sectional questionnaire and the sample used is 385 respondents. The results of the research are Concern for Other independent variables, Helping the company and destination image partially have significant positive influence on visiting decisions. While Expressing positive filling variables did not have a significant effect on visiting decisions. However, simultaneously Concern for Other, Expressing positive filling, Helping the company and the destination image have a significant positive effect on the dependent variable of visiting decisions. While the destination image variable is considered as the dominant variable in influencing tourists visiting decisions to Tikus island BengkuluKeywords: Consumer Satisfaction, Destination Image, Electronic Word of Mouth, Visiting Decision